2012
DOI: 10.1016/j.actpsy.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Deduction without awareness

Abstract: We investigated whether two basic forms of deductive inference, Modus Ponens and Disjunctive Syllogism, occur automatically and without awareness. In Experiment 1, we used a priming paradigm with a set of conditional and disjunctive problems. For each trial, two premises were shown. The second premise was presented at a rate designed to be undetectable. After each problem, participants had to evaluate whether a newly-presented target number was odd or even. The target number matched or did not match a conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The use of disjunctive arguments would also allow us to determine whether the findings can be extended to these more complex inferences. Reverberi et al (2012) found that disjunctive arguments did not produce the same priming effects as MP arguments, proposing that disjunctions require more effortful processing. Additionally, Handley et al (2011) replicated their initial findings using disjunctive arguments.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of disjunctive arguments would also allow us to determine whether the findings can be extended to these more complex inferences. Reverberi et al (2012) found that disjunctive arguments did not produce the same priming effects as MP arguments, proposing that disjunctions require more effortful processing. Additionally, Handley et al (2011) replicated their initial findings using disjunctive arguments.…”
Section: Methodsmentioning
confidence: 94%
“…It has been argued that MP inferences are drawn automatically through direct rules of inference (Braine & O'Brien 1991) that can be triggered by subliminal stimuli and carried out automatically, even without instructions (Reverberi, Burigo, & Cherubini, 2009;Reverberi, Pischedda, Burigo, & Cherubini, 2012;Rips, 1988). However, in Experiment1, MP arguments were influenced, albeit to a small extent, by a secondary load, which suggests that they are not implicit in nature.…”
Section: Discussionmentioning
confidence: 99%
“…While conscious reasoning often feels like a whirlwind of ''mental chaos'' (Siegel 2017, 99), unconscious inference seems to be automatic and syntactic. When subjects are presented with a semantically sparse but syntactically well-formed sentence like 'If there is a 3 then there is an 8', and are then subliminally presented with '3', they show facilitation for '8' (Reverberi et al 2012). Subliminally presenting '8', however, does not facilitate '3'.…”
Section: Concepts Inference and The Representational Theory Of Mindmentioning
confidence: 99%
“…There is more recent evidence that deductive inferences are performed automatically (Handley et al, 2011; also see Braine and O'Brien, 1998 for a compendium of results in the 'mental logic' research program) and unconsciously (Reverberi et al, 2012). This evidence suggests that inferential promiscuity is actualized independently of whether the subject knows about or endorses the relevant beliefs (see Quilty-Dunn and Mandelbaum, manuscript, for further discussion).…”
Section: Perceptual Beliefs Versus Perceptual Seemingsmentioning
confidence: 99%